PENERAPAN PERMENAKER NO 15 TAHUN 2005 DALAM PENGHEMATAN BIAYA PADA PERUSAHAAN PT ABC - Muhammad Mualif; Meina Wulansari Yusniar; Dian Masita Dewi (JWM (JURNAL WAWASAN MANAJEMEN), 2018)
PT ABC implemented a policy regarding the basic changes of calculation of overtime wages for non-staff employees according to the memo published by the company concerning the implementation of overtime wage calculation system based on the regulation of the Permenaker no 15 year 2005. This research is conducted to determine whether the implementation of Permenaker no 15 year 2005 at PT ABC as the basic calculation of overtime wages for non staff employees makes PT ABC more efficient or not. This research is a descriptive quantitatif. The research variables are salary and overtime payment. The population of this research is non staff employees as many as 2.615 people. The data used is secondary data. The result of this research showed that implementation of Permenaker no 15 year 2005 makes PT ABC save the cost 20% in the payroll period of September 2013 compared to before it was implemented.